MEKTEPLERDE ATOM FIZIKASÍ BÓLIMIN OQÍTÍWDÍ JETILISTIRIW JOLLARÍ (Mektep fizika muǵallimlerine metodikalıq járdem) - Jumamuratov, A.J.; Kalilaev, F.K. (ILIM hám JÁMIYET, 2022)
It is analyzed the methods of increasing the effectiveness of teaching in atomic, nuclear and elementary particle physics in schools with the help of innovative technologies.
Keywords: ta’lim texnologiyası; rejalashtirilgan bloklar; Tomson modeli; Bor pastulatlari; Frank Gerts tajribasi. Shtern-Gerlax tajribasi; spin